"Changed our lives": Psychosocial issues experienced by families of early adolescents with leukemia. (February 2022) - Chodidjah, Siti; Kongvattananon, Puangpaka; Liaw, Jen J.
Abstract: Purpose: This research aimed to explore psychosocial problems experienced by families of early adolescents with leukemia. Method: This phenomenology research was done during December 2019–August 2020 and involved eighteen families (47 family members) of early adolescents (10–14 years old) with leukemia. Participants were recruited by using purposive sampling and snowball techniques. Data were collected by using in-depth interviews and non-participatory observations until data saturation. Content analysis was used for data analysis. Member checking and triangulation methods were confirmed for trustworthiness. Results: The families' perception on psychosocial problem experiences included three themes and nine sub-themes. The first theme was dealing with adolescent' emotional changes with sub-themes, namely, emotional responses to the illness, compensation for the suffering, and self-showing. The second theme was parents' social isolation with sub-themes, namely, cancer-stigma, burden of care, and jealousy to non-cancer families. The last theme was emotional distress struggles with sub-themes, namely, feeling worried, guilty, and depressed. Conclusion: Leukemia diagnosis in early adolescents causes psychosocial problems affecting the family lives. Health care providers need to concern and support the families and the adolescents so that they can pass through the difficulties with positive adjustments. Highlights: Leukemia diagnosis and treatment caused emotional changes in adolescents with leukemia which caused psychosocial problems in the families. The effort to protect the adolescents from being harmed by peers and feeling jealousy to non-cancer families caused social limitation of the parents. The hardship in taking care of adolescents with leukemia may cause the parent experience severe depression and thinking of ending their own life.